Bioactivation of cyclopropyl rings by P450: an observation encountered during the optimisation of a series of hepatitis C virus NS5B inhibitors. (2nd December 2018) - Zhuo, Xiaoliang; Wang, Ying-Zi; Yeung, Kap-Sun; Zhu, Juliang; Huang, Xiaohua Stella; Parcella, Kyle E.; Eastman, Kyle J.; Kadow, John F.; Meanwell, Nicholas A.; Shu, Yue-Zhong; Johnson, Benjamin M.
Abstract: 1. Due to its unique C–C and C–H bonding properties, conformational preferences and relative hydrophilicity, the cyclopropyl ring has been used as a synthetic building block in drug discovery to modulate potency and drug-like properties. During an effort to discover inhibitors of the hepatitis C virus non-structural protein 5B with improved potency and genotype-coverage profiles, the use of a pyrimidinylcyclopropylbenzamide moiety linked to a C6-substituted benzofuran or azabenzofuran core scaffold was explored in an effort to balance antiviral potency and metabolic stability. 2. In vitro metabolism studies of two compounds from this C6-substituted series revealed an NADPH-dependent bioactivation pathway leading to the formation of multiple glutathione (GSH) conjugates. Analysis of these conjugates by LC-MS and NMR demonstrated that the cyclopropyl group was the site of bioactivation. Based on the putative structures and molecular weights of the cyclopropyl-GSH conjugates, a multi-step mechanism was proposed to explain the formation of these metabolites by P450. This mechanism involves hydrogen atom abstraction to form a cyclopropyl radical, followed by a ring opening rearrangement and reaction with GSH. 3. These findings provided important information to the medicinal chemistry team which responded by replacing the cyclopropyl ring with a gem-dimethyl group. Subsequent compounds bearing this feature were shown to avert the bioactivation pathways in question.